Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1091/mbc.11.12.4105
|View full text |Cite
|
Sign up to set email alerts
|

Human Orthologs of Yeast Vacuolar Protein Sorting Proteins Vps26, 29, and 35: Assembly into Multimeric Complexes

Abstract: Sorting nexin (SNX) 1 and SNX2 are mammalian orthologs of Vps5p, a yeast protein that is a subunit of a large multimeric complex, termed the retromer complex, involved in retrograde transport of proteins from endosomes to the trans-Golgi network. We report the cloning and characterization of human orthologs of three additional components of the complex: Vps26p, Vps29p, and Vps35p. The close structural similarity between the yeast and human proteins suggests a similarity in function. We used both yeast two-hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
284
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(308 citation statements)
references
References 24 publications
(42 reference statements)
15
284
3
1
Order By: Relevance
“…We verified a direct interaction between the amino-terminal three fourths (a.a. 1-295) of EhVps26 (EhVps26⌬C) and the aminoterminal third (a.a. 1-305) of EhVps35 (EhVps35N) and between the carboxyl-terminal fourth (a.a. 583-757) of EhVps35 (EhVps35C) and EhVps29, as well as lack of interaction between EhVps26 and EhVps29 by yeast two-hybrid system (unpublished data). These interactions are similar to those found for the mammalian retromer complex (Haft et al, 2000). On the other hand, we failed to detect the binding between EhRab7A (neither wild-type nor GTP-locked form) and EhVps26 (full-length, amino-, or carboxyl-terminus; unpublished data), which indicates that the interaction is transient and weak in this assay system.…”
Section: Molecular Biology Of the Cell 5298supporting
confidence: 86%
See 3 more Smart Citations
“…We verified a direct interaction between the amino-terminal three fourths (a.a. 1-295) of EhVps26 (EhVps26⌬C) and the aminoterminal third (a.a. 1-305) of EhVps35 (EhVps35N) and between the carboxyl-terminal fourth (a.a. 583-757) of EhVps35 (EhVps35C) and EhVps29, as well as lack of interaction between EhVps26 and EhVps29 by yeast two-hybrid system (unpublished data). These interactions are similar to those found for the mammalian retromer complex (Haft et al, 2000). On the other hand, we failed to detect the binding between EhRab7A (neither wild-type nor GTP-locked form) and EhVps26 (full-length, amino-, or carboxyl-terminus; unpublished data), which indicates that the interaction is transient and weak in this assay system.…”
Section: Molecular Biology Of the Cell 5298supporting
confidence: 86%
“…Because of the lack of these two components, the E. histolytica retromerlike complex likely plays a different role. Size fractionation by gel filtration revealed that the amoebic retromerlike complex showed an apparent molecular weight of 300 -500 kDa (unpublished data), which is comparable to that in mammalian cells (Haft et al, 2000). The missing components, sorting nexins and Vps5/17, possess PX domain and BAR domain for the interaction with phosphatidyl inositol 3-phosphate and the curbed membrane (Seaman and Williams, 2002;Habermann, 2004;Seaman, 2005).…”
Section: Identification Of a Retromerlike Complex As A Novel Ehrab7a mentioning
confidence: 84%
See 2 more Smart Citations
“…Since then, retromer has been implicated in a broad range of protein-sorting pathways and has most recently been shown to be required for the maintenance of proper Wnt secretion in the development of both Caenorhabditis elegans and Drosophila melanogaster (Belenkaya et al, 2008;Franch-Marro et al, 2008;Pan et al, 2008;Port et al, 2008;Yang et al, 2008), underscoring its importance in retrograde transport. In yeast retromer is composed of five proteins that assemble into two subcomplexes: Vps5 and Vps17 (Snx1/ Snx2 and Snx5/Snx6 in mammals) and Vps26, Vps29, and Vps35 (and the homologous proteins in metazoans; Seaman et al, 1998;Haft et al, 2000;Wassmer et al, 2007). Vps5 and Vps17 are members of the sorting nexin family of proteins and are responsible for localizing the retromer complex to tubular endosomal membranes via the concerted action of their BAR (Bin/Amphiphysin/RVS) and PX (phox homology) domains (Carlton et al, 2004;Seet and Hong, 2006).…”
Section: Introductionmentioning
confidence: 99%